Assessment of Fatty Liver Syndrome and Its Predisposing Factors in a Dairy Herd from Venezuela. (27th April 2013) - Gonzalez, Clara I.; Rosendo, Oswaldo
Abstract : The present on-farm research evaluated the occurrence of fatty liver syndrome and its predisposing risk factors for multiparous dairy cows from a commercial herd in Venezuela. Liver biopsy samples were collected at 35 days (d) prepartum (Holstein, n = 14 ; Holstein × Carora crossbred, n = 17 ) as well as 1 to 7 d (Holstein, n = 8 ; Holstein × Carora crossbred, n = 11 ) and 28 to 35 d (Holstein, n = 6 ; Holstein × Carora crossbred, n = 14 ) postpartum in order to analyse hepatic triacylglycerols (TAG, % wet basis) and glycogen concentrations. At postpartum, an occurrence of 72.0% for severe fatty liver along with 73.5% of subclinical ketosis (SCK) was found. The multiple regression model that best explained the association between milk production in the previous lactation (MYP) and TAG at first week postpartum was as follows: TAG, % = −11.2 + 3.16 (prepartum body condition) + 0.0009176 (MYP) (R ² = 0.36, P < 0.05 ). Logistic regression indicated that Holstein × Carora crossbred cows tended to have 27% higher relative risk than Holstein to experience SCK, whereas prepartum liver TAG greater than 3% tended to be associated with a higher relative risk for SCK compared to cows with TAG ≤3%.